PERSEPSI WISATAWAN TERHADAP OBJEK DAYA TARIK WISATA DI KEBUN RAYA LIWA KABUPATEN LAMPUNG BARAT - Meri Wulandari; Gunardi Djoko Winarno; Agus Setiawan; Arief Darmawan (Forestry Study Program University Of Mataram, 2019)
The perception of tourists attraction was very important to be learnt to provide some information for manager to object tourism attraction. The purpose of this research was to analyzed the perceptions of tourists to the objects tourism attractions, accommodation, infrastructure, facilities and services at the Botanical Garden of Liwa. The method used was a questionnaire. The results of this research showed that Liwa Botanical garden has 5 objects tourism attractions that were Ornamental Garden, Fruit Garden, Araceae Garden, Aren Garden and Photo Spot . Araceae Garden, and Aren Garden had the lowest score based on the tourist perception. The highest tourist perception value is the Photo Spot; while the tourist perception of Araceae Park and Aren Park has the lowest value that is classified as not good because the object has not been opened for tourists. Perception of infrastructure was higher than accommodation, facilities and service. Development need to be carried especially in tourist lodgings, objects tourism attraction, the parking area and promotion to introduce Liwa Botanical Garden to the tourists.